Emotional regulation and burnout prevention: psychological contributions to sustainable social work practice - Cădariu, Ioana-Eva; Rad, Dana (Technium Social Sciences Journal, 2025)
Burnout remains a common threat to the viability of social work practice, sustained by chronic emotional exhaustion, depersonalization, and diminished personal accomplishment. In answer, this article reviews the crucial role of emotional regulation in the prevention of burnout and professional resilience. Grounded in key psychological models—namely mindfulness, cognitive reappraisal, and acceptance processes—this research underscores the prominence of emotional regulation as a core buffering factor against occupational stress. We examine the integration of emotional regulation skills into practice at the individual level, organizational interventions such as supervisory and peer support systems, and emotionally supportive institutional cultures. Recent research and meta-analyses are incorporated to demonstrate the advantages of emotional regulation training in reducing burnout and enhancing well-being. Future directions emphasize the significance of richer training curricula, systemic level organizational reforms, responsible use of technological supports, and longitudinal studies in different social work settings. By putting emotional regulation at the forefront of professional education and practice, the social work profession can embark on a more sustainable, resilient, and ethically motivated future.